Untersuchungen an a-C:H:Me-beschichteten Rillenkugellagern unter Trockenlaufbedingungen - Kröner, Julia; Tremmel, Stephan; Wartzack, Sandro (Tribologie und Schmierungstechnik, 2019)
Under extreme environmental conditions or due to restrictions oil- or grease-lubricated standard rolling bearings can only be used to a limited extent or not at all. Existing solutions are expensive due to the special materials or lubricants used or have only a very limited service life. The alternative approach presented here involves the use of cost-effective standard rolling bearings, which have been modified with a friction and wear-reducing coating on individual components of the rolling bearing. Radial deep groove ball bearings of type 6206 are tested in operating life tests on a four bearing test rig. All investigated coating systems are described in the literature as basically usable under dry running conditions and normal atmosphere: Graphite, titanated molybdenum disulfide (MoS2:Ti), a modified (a-C:H:X) and a metal-containing hydrogen-containing amorphous carbon coating (a-C:H:Me). The different coating systems were applied to the raceways of the rolling bearing using PVD or PACVD processes and tested with both steel and ceramic balls. The results of these experiments in terms of operating life, tribological behaviour and, in particular, the repeatability of the results will be presented in this paper.<br
Keywords: Trockenlauf; Rillenkugellager; PVD-Beschichtung; Amorphe Kohlenstoffschicht; Bauteiltest; Vier-Lager- Prüfstand; Gebrauchsdauer